Geography and social and environmental education: practices and experiences with primary school students in Catalão (GO) - Katarina Santos, Leonoura; Macêdo, Robério Francisco de; Bertazzo, Cláudio José (Revista Ensino de Geografia (Recife), 2021)
The article describes interventions and a didactic sequence of socio-environmental education with a special focus on agroecological principles. The article aims to demonstrate initiatives for Socio-Environmental and Agroecological Education interventions and highlight their relevance for the training of Basic Education students - Elementary School Stage. In the teaching methodology of the classes, playful perspectives were used, based on games, waste segregation practices and, in a gamified environment, an Agroecological Quiz; finally, a survey was carried out with the students, inducing reflection on the quality of life of people, as well as the internalized knowledge on such themes. Theteaching situations were developed at the State School of Education Matilde Margon Vaz in the city of Catalão (GO), in partnership with the Center for Studies, Research and Extension in Agroecology (NEPEA); integrating the discipline of Supervised Internship in Geography II. The results show a deepening of learning and the internalization of the concepts discussed in the didactic units. It is concluded that didactic experience with alternatives and teaching techniques focused on the student and his / her learning, lead to the increase of conceptual repertoire on themes of Geography of Nature, such as, for example, Socioenvironmental and Agroecological Education.